Arctic sea ice associated biodiversity: importance and challenges. - Barry, Tom (2011)
Mr. Tom Barry, CAFF – Conservation of Arctic Flora and Fauna, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.